2011
DOI: 10.2136/sssaj2010.0279
|View full text |Cite
|
Sign up to set email alerts
|

XANES and Pyrolysis-FIMS Evidence of Organic Matter Composition in a Hummocky Landscape

Abstract: The quantity and quality of soil organic N and C are strongly influenced by variations in landscape position and management practices such as cultivation. In this study, we used synchrotron-based C and N AT-edge x-ray absorption near-edge structure (XANES) spectroscopy coupled with pyrolysis-field ionization mass spectrometry (Py-FIMS) to explore C and N chemistry among soils obtained from dilferent landscape positions along a hummocky transect and from locations under different management practices. A distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 92 publications
(72 reference statements)
2
10
3
Order By: Relevance
“…The decreasing abundance of sterols with soil depth is due to the lower input of plant materials, since sterols originating from octacosanol/nonacosanol at, m/z 392/406 ( Figure 3) [55,56], are of a plant origin. The relative proportions of alkylaromatics in the summit soil are comparable to those reported for the well-drained cultivated soils by Py-FIMS analysis [57,58]. The thermal stability of alkylaromatics showed no variation with soil depth and, thus, the greater proportion of alkylaromatics in subsoils is not due to the increased protection with soil depth.…”
Section: Variation In Organic Matter Chemistry With Depthsupporting
confidence: 75%
“…The decreasing abundance of sterols with soil depth is due to the lower input of plant materials, since sterols originating from octacosanol/nonacosanol at, m/z 392/406 ( Figure 3) [55,56], are of a plant origin. The relative proportions of alkylaromatics in the summit soil are comparable to those reported for the well-drained cultivated soils by Py-FIMS analysis [57,58]. The thermal stability of alkylaromatics showed no variation with soil depth and, thus, the greater proportion of alkylaromatics in subsoils is not due to the increased protection with soil depth.…”
Section: Variation In Organic Matter Chemistry With Depthsupporting
confidence: 75%
“…Despite strong differences observed between soil organic matter components in whole soil samples using XANES and Py-FIMS (Gillespie et al 2011b), no patterns of differences were found between GRSP extracted from different soils. This implies that GRSP is either uniform across soils or that the extraction method favors the production/extraction of similar substances.…”
Section: General Findings the Molecular Characterization Of Glomalin-mentioning
confidence: 68%
“…Glomalin-related soil protein was obtained using the citrate extraction and autoclaving method and soils from a landscapescale study described elsewhere (Gillespie et al 2011b). We demonstrated that XANES and Py-FIMS were useful for describing the bulk GRSP mixture as well as the composition of the non-proteinaceous materials (Gillespie et al 2011a).…”
Section: General Findings the Molecular Characterization Of Glomalin-mentioning
confidence: 96%
“…Carbohydrates are a preferentially degraded carbon form, and are released from decomposing polysaccharides. Carbohydrate content tends to decrease as decomposition proceeds (Kögel-Knabner 2000; Gillespie et al 2011). One study of temperate soils found that carbohydrates were lower in depleted soil where fertilizer was not applied, due to lower plant inputs and greater turnover of those inputs (Kiem et al 2000).…”
Section: Yield Average and Trendsmentioning
confidence: 99%